Donepezil Improved Cognitive Deficits in a Patient With Neurosyphilis. Issue 4 (July 2015) - Wu, Yi-Shan; Lane, Hsien-Yuan; Lin, Chieh-Hsin
<x xml:space="preserve">Abstract</x> Abstract A large number of patients with neurosyphilis present dementia with a progressive course and psychiatric symptoms such as depression, mania, and psychosis. Despite prompt and proper antibiotic treatment, the recovery is often incomplete, especially when tissue damage has occurred. We reported a patient with persisted cognitive decline associated with neurosyphilis that improved substantially after donepezil therapy. A 43-year-old man manifested significant psychiatric symptoms such as mania, psychosis, and cognitive impairment due to neurosyphilis. Subsequently, the patient was treated with antipsychotics and donepezil concurrent with an adequate antibiotic treatment for neurosyphilis. During the 1-year follow-up, his rapid plasma reagin titer approached from 1:256 to 1:64. His Mini-Mental State Examination (MMSE) and Alzheimer's Disease Assessment Scale-cognitive subscale scores improved from 12 to 25 and 42.3 to 6.3, respectively, after a 6-month donepezil treatment. Donepezil was discontinued. Three months later, worsening of cognitive impairment (MMSE score, 23) was noted. After donepezil was started again for 3 months, his MMSE score improved to 26. Persistent cognitive impairment is commonly associated with neurosyphilis despite adequate penicillin treatment. Treatment of the cognitive impairment is important but difficult. Cholinergic pathways are considered as involving in the cognitive deficit induced by neurosyphilis and donepezil, a cholinesterase inhibitor, which may be useful for the improvement of cognition. In this case report, we described for the first time the successful use of donepezil in treating cognitive impairment associated with neurosyphilis. The role of cholinesterase inhibitors in the treatment of cognitive impairments caused by neurosyphilis needs further studies.